Management and Leadership Comparative Study (International Journal of Innovative Research in Engineering & Management, 2021)
The objective of this article is to analyses new concepts for  leadership and management and create a new impression known  as the Mirror Leadership. If a company has to develop new  eaders, it gives employee managers an image of their leadership  elegance. Management and leadership differ significantly. The  first addresses doubts and the latter addresses change and the  management and administration of all groups together. Any  strategy of action requires defining what will be achieved,  creating interpersonal relationships with those that may help to  achieve a common goal, and lettering an item to ensure that  particular personnel undertake their work. Each personthese three behaviors differently. Most businesses must  strengthen their leadership skills. Successful organizations should not wait until leaders appear. Successful firms look to young  leaders and put them in areas that they don't know about to  support them. With careful study, education and incentive more  individuals are leading within organizations.
Keywords: Behavior; Interpersonal Relations; Leadership; Leading; Management; Manager; Organizational